Suture line and preparation method thereof
By combining piezoelectric materials and magnetostrictive fillers on the sutures and modifying the hydrogel, the complexity and biosafety problems of existing exogenous electrical stimulation devices are solved, and electrical stimulation induced by wireless magnetic field is achieved. Promote wound healing, reduce wound friction damage, and has wide application prospects.
Patent Information
- Application Number
- CN202411300202.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-17
AI Technical Summary
Due to its complex structure, dependence on external power supplies and low biosafety, existing exogenous electrical stimulation devices are difficult to achieve non-invasive electrical stimulation with controllable response intensity, and are prone to inflammation and infection, hindering wound healing.
Develop a suture line including piezoelectric materials and magnetostrictive fillers, which can be induced in a wireless magnetic field by modifying the hydrogel on the surface of the suture core material to form a low friction, adapted tissue modulus. Electrical stimulation is generated to promote wound healing.
It realizes the generation of electrical stimulation under the wireless magnetic field, promotes cell migration and proliferation, simplifies the preparation process, reduces wound friction damage, and has broad application prospects.
Smart Images

Figure CN119318729A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical materials, and in particular to a suture thread and a preparation method thereof. Background Art
[0002] Skin wounds are one of the most important health issues in the world. Skin wound repair and tissue regeneration is a complex process involving multiple physiological signals. Effective and rapid wound healing is of great significance for avoiding excessive inflammation, relieving pain, and restoring biological functions. However, effective and rapid wound healing still faces huge challenges.
[0003] Exogenous electrical stimulation can significantly promote wound healing. However, most power generation devices and materials are limited by their complex structure, dependence on external power sources, and low biosafety. Traditional physical stimulation relies on invasive exogenous devices, which makes it difficult to accurately adjust the dose and spatial range of external physical stimulation. To make matters worse, exogenous devices, such as electrical stimulation electrodes, can easily induce inflammation and infection, hinder wound healing, prolong treatment time, and limit their widespread application. Therefore, it would be of great significance to develop a non-invasive electrical stimulation suture with simple process, rapid preparation, good response effect, and controllable response intensity.
[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0005] Based on the above-mentioned deficiencies of the prior art, the object of the present invention is to provide a suture and a preparation method thereof, aiming to provide a non-invasive electrical stimulation suture with controllable response intensity.
[0006] The technical solution of the present invention is as follows:
[0007] In a first aspect of the present invention, there is provided a suture, wherein the suture comprises a suture core material and a hydrogel modified on the surface of the suture core material;
[0008] The suture core material comprises the following components by mass:
[0009] 1 to 1000 parts of piezoelectric material and 1 to 1000 parts of magnetostrictive filler.
[0010] Optionally, the hydrogel is coated on the surface of the suture core material.
[0011] Optionally, the piezoelectric material includes at least one of boron nitride nanotubes, 3-hydroxybutyric acid-co-3-hydroxyvaleric acid, collagen, diphenylalanine, N-vinylglycine, poly(L-lactic acid), cellulose, polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene, lead zirconate titanate, barium titanate and potassium sodium titanate.
[0012] Optionally, the magnetostrictive filler has a core-shell structure, wherein the core material includes at least one of iron-nickel alloy, cobalt-iron alloy, ferrite, rare earth alloy and gallium-antimony alloy, and the shell material includes at least one of boron nitride nanotubes, 3-hydroxybutyric acid-co-3-hydroxyvaleric acid, collagen, diphenylalanine, N-vinylglycine, L-polylactic acid, cellulose, polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene, lead zirconate titanate, barium titanate and potassium sodium titanate.
[0013] A second aspect of the present invention provides a method for preparing the suture thread as described above, comprising the following steps:
[0014] Adding 1 to 1000 parts by mass of piezoelectric material and 1 to 1000 parts by mass of magnetostrictive filler into a solvent to obtain a mixed solution;
[0015] The mixed solution is extruded into a coagulation bath solution and allowed to remain there for a preset time, and the solvent is exchanged while being shaped to obtain a linear composite material;
[0016] The linear composite material is dried and annealed, and then corona polarized to obtain a suture core material;
[0017] The suture is obtained by modifying the surface of the suture core material with hydrogel.
[0018] Optionally, the ratio of the volume of the solvent to the total mass of the piezoelectric material and the magnetostrictive filler is (50-150) mL: (10-50) g;
[0019] The solvent includes at least one of dimethyl sulfoxide, N-methylpyrrolidone, dimethylformamide, isopropanol, phosphate buffer and ethanol.
[0020] Optionally, the coagulation bath solution includes at least one of deionized water, phosphate buffer, methanol, ethanol and isopropanol; and the preset time is 1 to 12 hours.
[0021] Optionally, the drying temperature is 60-120° C., and the drying time is 6-36 hours; the annealing temperature is 90-180° C., and the annealing time is 1-12 hours.
[0022] Optionally, the conditions of the corona polarization are:
[0023] The temperature is 25-50°C, the time is 10-60 minutes, and the voltage is 5-30 kV.
[0024] Optionally, the method further includes a step of evacuating the mixed liquid before extruding the mixed liquid into the coagulation bath solution and allowing the mixed liquid to remain there for a preset time.
[0025] Beneficial effects: The suture provided by the present invention is compatible with the tissue modulus, has low friction, and has good magnetic field response electrical stimulation capabilities while maintaining the basic properties of piezoelectric materials. It has non-invasive electrical stimulation characteristics with controllable response intensity, and can generate electrical stimulation under the induction of wireless magnetic fields, thereby promoting cell migration and proliferation, and promoting wound healing. And because the suture has low friction, it will basically not cause further friction damage to the wound when the suture is removed, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagram of the preparation process flow of the suture thread in Example 1 of the present invention.
[0027] Figure 2 (a) is a bending macroscopic morphology image of the suture prepared in Example 1 of the present invention, (b) is a knotting macroscopic morphology image of the suture prepared in Example 1 of the present invention, (c) is a cross-sectional SEM image of the suture prepared in Example 1 of the present invention, and (d) is a surface SEM image of the suture prepared in Example 1 of the present invention.
[0028] Figure 3 This is a graph showing the mechanical properties of the suture thread prepared in Example 1 of the present invention.
[0029] Figure 4 This is a graph showing the cyclic tensile performance results of the suture thread prepared in Example 1 of the present invention.
[0030] Figure 5 (a) is the hysteresis loop diagram of the suture thread prepared in Example 1 of the present invention, and (b) is the hysteresis loop diagram of the suture thread prepared in Example 1 of the present invention.
[0031] Figure 6 This is a graph showing the electrical release ability of the suture prepared in Example 1 of the present invention under a specific magnetic field.
[0032] Figure 7 (a) is a wound slice 3 days after the wound was sutured with commercial PLGA sutures, and (b) is a wound slice 3 days after the wound was sutured with the sutures prepared in Example 1 of the present invention.
[0033] Figure 8 (a) is a schematic diagram of the friction coefficient test method, and (b) is a diagram showing the friction coefficient results of the suture prepared in Example 1 and the commercial PLGA suture for different types of tissues. DETAILED DESCRIPTION
[0034] The present invention provides a suture and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0035] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0036] An embodiment of the present invention provides a suture, wherein the suture includes a suture core material and a hydrogel modified on the surface of the suture core material;
[0037] The suture core material comprises the following components by mass:
[0038] 1 to 1000 parts of piezoelectric material and 1 to 1000 parts of magnetostrictive filler.
[0039] The suture provided by the present invention is adapted to the tissue modulus, has low friction (due to the presence of hydrogel, friction and protein adsorption can be reduced), has certain mechanical strength and biocompatibility, and maintains the basic characteristics of piezoelectric materials while also having good magnetic field response electrical stimulation capabilities, non-invasive electrical stimulation characteristics with controllable response intensity, and good magnetic field induced electrical stimulation capabilities. It can generate electrical stimulation under wireless magnetic field induction (i.e., it has wireless magnetic field stimulation electrical release capabilities), thereby promoting cell migration and proliferation, and promoting wound healing. And because the suture has low friction, it will basically not cause further friction damage to the wound when the suture is removed, and has broad application prospects.
[0040] In some embodiments, the mass ratio of the piezoelectric material to the magnetostrictive filler is 1:1, 1:2, 1:5, 1:10, 1:100, 1:200, 1:300, 1:400, 1:500, 1:600, 1:700, 1:800, 1:900 or 1:1000, 2:1, 2:10, 2:100, 2:500, 2:100, 5:1, 5:2, 500:1, 500:2, 1000:1 or 1000:2, etc.
[0041] In some embodiments, the hydrogel is coated on the surface of the suture core material.
[0042] In some embodiments, the piezoelectric material includes at least one of boron nitride nanotubes, 3-hydroxybutyric acid-co-3-hydroxyvaleric acid, collagen, diphenylalanine, N-vinylglycine, poly(L-lactic acid), cellulose, polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene, lead zirconate titanate, barium titanate, and potassium sodium titanate, but is not limited thereto.
[0043] In some embodiments, the magnetostrictive filler has a core-shell structure, wherein the core material includes at least one of iron-nickel alloy, cobalt-iron alloy, ferrite (such as nickel ferrite, cobalt ferrite, etc.), rare earth alloy and gallium-antimony alloy, and the shell material includes at least one of boron nitride nanotubes, 3-hydroxybutyric acid-co-3-hydroxyvaleric acid, collagen, diphenylalanine, N-vinylglycine, L-lactic acid, cellulose, polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene, lead zirconate titanate (such as lead zirconate titanate, etc.), barium titanate and potassium sodium titanate.
[0044] An embodiment of the present invention further provides a method for preparing the suture thread as described above, comprising the following steps:
[0045] S1. Add 1 to 1000 parts by mass of piezoelectric material and 1 to 1000 parts of magnetostrictive filler into a solvent to obtain a mixed solution;
[0046] S2, extruding the mixed solution into a coagulation bath solution and leaving it for a preset time, exchanging the solvent and achieving shaping, to obtain a linear composite material;
[0047] S3, drying and annealing the linear composite material, and then performing corona polarization to obtain a suture core material;
[0048] S4, modifying the hydrogel on the surface of the suture core material to obtain the suture.
[0049] In an embodiment of the present invention, piezoelectric material and magnetostrictive filler are added to a solvent, stirred and mixed to obtain a mixed solution, and bubbles are removed by vacuuming, and a suture with wireless magnetic field stimulation and electrical release is prepared by extrusion, coagulation bath solution exchange (the solvent is discharged by coagulation liquid exchange to achieve qualitative purposes), drying (the purpose is to remove residual solvent and coagulation bath solution), annealing, corona polarization, and growth of hydrogel. The preparation method provided by the present invention is simple and fast, the raw materials are easily available, the process flow is short, and it is easy to operate. The suture prepared by the preparation method provided by the embodiment of the present invention is adapted to the tissue modulus, has low friction (due to the presence of hydrogel), has certain mechanical strength and biocompatibility, and maintains the basic properties of piezoelectric materials while also having good magnetic field response electrical stimulation ability, non-invasive electrical stimulation characteristics with controllable response intensity, and good magnetic field induced electrical stimulation ability. It can generate electrical stimulation under wireless magnetic field induction (that is, it has wireless magnetic field stimulation electrical release ability), thereby promoting cell migration and proliferation, and promoting wound healing. And because the suture has low friction, it will basically not cause further friction damage to the wound when the suture is removed, and has broad application prospects.
[0050] In step S1, in some embodiments, the ratio of the volume of the solvent to the total mass of the piezoelectric material and the magnetostrictive filler is (50-150) mL: (10-50) g. For example, the ratio of the volume of the solvent to the total mass of the piezoelectric material and the magnetostrictive filler is 50:10, 50:25, 50:50, 70:10, 70:25, 70:50, 90:10, 90:25, 90:50, 100:10, 100:25, 100:50, 150:10, 150:25, 150:50, etc.
[0051] In some embodiments, the solvent includes at least one of dimethyl sulfoxide, N-methylpyrrolidone, dimethylformamide, isopropanol, phosphate buffer, and ethanol.
[0052] In some embodiments, 1 to 1000 parts by mass of piezoelectric material and 1 to 1000 parts of magnetostrictive filler are added to a solvent, and stirred at a rotation speed of 60 to 1440 rpm for 0.5 to 2 hours to obtain a mixed solution.
[0053] Stirring at a speed of 60 to 1440 rpm for 0.5 to 2 hours can ensure uniform stirring to obtain a mixed solution. In addition, ultrasonic dispersion can also be performed during the stirring process.
[0054] As an example, the stirring speed can be 60rpm, 100rpm, 200rpm, 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 800rpm, 900rpm, 1000rpm, 1100rpm, 1200rpm, 1300rpm, 1400rpm or 1440rpm, and the stirring time can be 0.5h, 1h, 1.5h or 2h, etc.
[0055] In some embodiments, the method for preparing the magnetostrictive filler having a core-shell structure comprises the following steps:
[0056] Providing magnetostrictive filler nanoparticles;
[0057] Modifying the surface of the magnetostrictive filler with an adsorbent (such as oleic acid, dopamine hydrochloride, etc.) to obtain magnetostrictive filler nanoparticles coated with the adsorbent;
[0058] Dispersing the magnetostrictive filler nanoparticles wrapped by the adsorbent in an organic solvent (such as ethanol), then adding a first shell precursor material, and then adding a second shell precursor material to obtain a mixed solution;
[0059] The mixed solution is reacted at a preset temperature (the first shell precursor material reacts with the second shell precursor material to form a shell material on the surface of the magnetostrictive filler nanoparticles) to obtain the magnetostrictive filler with a core-shell structure.
[0060] Specifically, taking the core material as cobalt ferrite nanoparticles and the shell material as barium titanate as an example, the preparation method of the magnetostrictive filler with a core-shell structure comprises the following steps:
[0061] Modifying the surface of cobalt ferrite nanoparticles with oleic acid to prepare oleic acid-coated cobalt ferrite nanoparticles;
[0062] The oleic acid-coated cobalt ferrite nanoparticles are dispersed in ethanol, and the mixture is uniformly mixed with an ethanol solution containing tetrabutyl titanate by ultrasonic stirring, and an aqueous solution containing barium acetate is slowly added dropwise until the mixture is uniformly stirred to obtain a mixed solution;
[0063] The mixed solution is placed in a 60°C water bath, the pH is adjusted to 3-4 and then allowed to stand for 2 hours, then the temperature is maintained at 90°C for 6 hours, and then maintained at 120°C for 12 hours, and the product is sintered at 600°C for 6 hours. The final product is a magnetostrictive filler with a core-shell structure.
[0064] In step S2, in some embodiments, the coagulation bath solution includes at least one of deionized water, phosphate buffer, methanol, ethanol and isopropanol, but is not limited thereto. The preset time is 1 to 12 hours, for example, the preset time is 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours or 12 hours. The preset time can ensure that the solvent is exchanged and fully discharged.
[0065] In some embodiments, the mixed solution is squeezed into the coagulation bath solution and kept there for a preset time, and the mixed solution is further vacuumed. The purpose of vacuuming is to remove bubbles so that the texture of the prepared suture core material is more uniform.
[0066] In step S3, in some embodiments, the drying temperature is 60 to 120° C., and the drying time is 6 to 36 hours. For example, the drying temperature is 60° C., 70° C., 80° C., 90° C., 100° C., 110° C., or 120° C., and the drying time is 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 15 hours, 18 hours, 20 hours, 25 hours, 28 hours, 30 hours, 32 hours, 35 hours, or 36 hours.
[0067] In some embodiments, the annealing temperature is 90-180°C, and the annealing time is 1-12h. For example, the annealing temperature is 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C, and the annealing time is 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h. The purpose of the annealing is to make the linear composite material crystallize better.
[0068] In some embodiments, the conditions of the corona poling are: a temperature of 25 to 50° C., a time of 10 to 60 min, and a voltage of 5 to 30 kV. For example, the temperature may be 25° C., 30° C., 35° C., 40° C., 45° C., or 50° C., etc. The time may be 10 min., 15 min., 20 min., 25 min., 30 min., 35 min., 40 min., 45 min., 50 min., 55 min., or 60 min. The voltage may be 5 kV, 10 kV, 15 kV, 20 kV, 25 kV, or 30 kV, etc.
[0069] In this embodiment, corona poling can be performed to stimulate the piezoelectric properties of the piezoelectric material.
[0070] In step S4, in some embodiments, the step of modifying the surface of the suture core material with hydrogel to obtain the suture specifically includes:
[0071] The suture core material is plasma cleaned (to open the molecular chains on the surface of the suture core material), then immersed in a hydrophilic and hydrophobic initiator solution (the hydrophilic and hydrophobic initiator may be benzophenone, and the solvent may be at least one of ethanol and isopropanol), and then immersed in a hydrogel precursor solution, and cured by ultraviolet light for 30 to 180 minutes (for example, it can be 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes, 90 minutes, 100 minutes, 110 minutes, 120 minutes, 130 minutes, 140 minutes, 150 minutes, 160 minutes, 170 minutes or 180 minutes, etc.), to form a hydrogel (as a hydrogel skin) on the surface of the suture core material.
[0072] In some embodiments, the hydrogel precursor solution includes a hydrogel precursor and a photoinitiator, and the solvent may be water. The hydrogel precursor includes acrylamide or [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide, and the photoinitiator is photoinitiator 2959 or α-ketoglutaric acid, wherein the structural formula of photoinitiator 2959 is In some embodiments, 0.1 to 10 g of plasma-cleaned suture core material is immersed in 10 to 200 mL of benzophenone solution (wherein the mass content of benzophenone is 2 to 20%, and the solvent may be at least one of ethanol and isopropanol) for 1 to 60 min, and then taken out and immersed in 10 to 1000 mL of hydrogel precursor solution (wherein the mass content of the hydrogel precursor is 10% to 50%, and the mass content of the photoinitiator is 0.5% to 5%) for 1 to 20 min. After UV curing for 30 to 180 min, a hydrogel is formed on the surface of the suture core material.
[0073] The present invention will be further described below by means of specific examples.
[0074] Example 1
[0075] This embodiment provides a method for preparing a suture based on controllable magnetic voltage and electricity, such as Figure 1 As shown, the following steps are included:
[0076] 1 g of nickel ferrite nanoparticles was added to 10 mL of dopamine hydrochloride aqueous solution, stirred at room temperature for 12 h in the dark, and air-dried at room temperature to obtain polydopamine-coated nickel ferrite nanoparticles; 234.38 mg of polydopamine-coated nickel ferrite nanoparticles were dispersed in 20 mL of ethanol, and then mixed with 20 mL of ethanol solution containing tetrabutyl titanate (the concentration of tetrabutyl titanate was 0.02 mol / L) by ultrasonic stirring, and 10 mL of an aqueous solution containing barium acetate (the concentration of barium acetate was 0.02 mol / L) was slowly added dropwise. The concentration is 0.02 mol / L), and the mixture is stirred until uniform to obtain a mixed solution; the mixed solution is placed in a 60°C water bath, an acetic acid solution is added to adjust the pH to 3-4, and then the mixed solution is allowed to stand for 2 hours, and then the temperature is maintained at 90°C for 6 hours, and then the temperature is maintained at 120°C for 12 hours, and the obtained product is placed at 600°C for sintering for 6 hours, and the final product is a magnetostrictive filler with a core-shell structure, namely, barium titanate-nickel ferrite core-shell particles (nickel ferrite is the core material, and barium titanate is the shell material);
[0077] 10 g of polyvinylidene fluoride-trifluoroethylene and 1 g of barium titanate-nickel ferrite core-shell particles were added to 100 mL of dimethyl sulfoxide, and the mixture was stirred at a speed of 180 rpm for 120 min to obtain a mixed solution, and the mixed solution was vacuumed to remove bubbles;
[0078] The vacuum-treated mixed solution was extruded into a coagulation bath solution (specifically, a mixed solution of ethanol and deionized water, with a volume ratio of ethanol to deionized water of 9:1) and allowed to remain there for 12 hours, while the dimethyl sulfoxide was exchanged and the mixture was shaped to obtain a linear composite material;
[0079] The linear composite material was dried at 60°C for 36 hours to completely remove residual dimethyl sulfoxide and residual coagulation bath solution, and then annealed and crystallized at 120°C for 6 hours, and then corona polarized at 25°C for 60 minutes with a voltage intensity of 30 kV to excite the piezoelectric properties of polyvinylidene fluoride-trifluoroethylene in the linear composite material to obtain a suture core material;
[0080] The surface of the suture core material is plasma treated for 15 minutes, and then 5 g of the plasma-treated suture core material is immersed in 50 mL of benzophenone ethanol solution (benzophenone mass content is 10%) for 25 minutes, and then immersed in 100 mL of hydrogel precursor solution (specifically an aqueous solution of 25 wt% acrylamide and 1 wt% photoinitiator 2959; wt% represents mass content, the same below) for 10 minutes. After taking out, it is irradiated with light of 400 nm wavelength for photocuring for 30 minutes, and then a layer of hydrogel skin is modified on the surface of the suture core material to reduce friction and protein adsorption, thereby obtaining the suture.
[0081] The suture prepared in Example 1 was tested and characterized:
[0082] (1) The macroscopic and microscopic morphology of the suture line Figure 2 As shown, Figure 2 (a) shows the flexibility of the suture. Figure 2 (b) shows the knot-tying performance of the suture. Figure 2 (c) is a cross-sectional scanning electron microscope (SEM) image of the suture line. Figure 2 (d) is the surface SEM image of the suture line.
[0083] (2) Perform a tensile test on the suture to obtain a stress-strain curve of the suture. The results are as follows: Figure 3 As shown, it can be seen that the suture thread prepared in Example 1 has good mechanical strength.
[0084] (3) The suture thread was subjected to a cyclic tensile test with a strain of 100%. The results are as follows: Figure 4 As shown, the results show that after 10,000 cycles of stretching, the suture prepared in Example 1 still has good mechanical strength.
[0085] (4) The magnetic hysteresis loop and the electrical hysteresis loop of the suture thread prepared in Example 1 are as follows: Figure 5 As shown in (a) and (b) in the figure, it is shown that the suture line has good response behavior to magnetic field and electric field respectively.
[0086] (5) Determine the strength of the applied magnetic field, change the frequency of the magnetic field, and collect the response voltage of the suture prepared in Example 1. Specifically, control the distance between the magnetic field and the suture test module, adjust the magnetic field strength to 100 mT, and change the magnetic field strength cyclically to ensure that the magnetic field regularly cuts the suture and achieves regular electrical release. The released voltage strength is collected and displayed by an oscilloscope. The results are as follows: Figure 6 As shown, a voltage of 40 mV can be released at a frequency of 3 Hz. It can be seen that under the stimulation of an external magnetic field, the suture prepared in Example 1 can be electrically released without connecting an external power supply.
[0087] (6) The suture prepared in Example 1 and the commercial polylactic acid-co-glycolic acid (PLGA) suture were used to suture the wound for 3 days, and then the sections were compared. The results were as follows: Figure 7 As shown, it can be seen that 3 days after the wound was sutured with the commercial PLGA suture, the epithelial tissue differentiation at the wound was not obvious, and inflammation occurred. However, 3 days after the wound was sutured with the suture prepared in Example 1, the epithelial tissue differentiation at the wound was obvious, and no obvious inflammation occurred.
[0088] (7) The friction coefficients of the suture prepared in Example 1 and the commercial PLGA suture on different types of tissues were tested. Figure 8 In (a), the suture is passed through the tissue and then weighed (100 g). One end of the suture is then fixed and the other end is pulled to test the friction coefficient. The results are shown in Figure 2. Figure 8 As shown in (b), it can be seen that the friction coefficient of the suture prepared in Example 1 (i.e., the controllable magnetic voltage electric suture in the figure) for different types of tissues (skin, Achilles tendon, intestine and liver) is lower than that of the commercial PLGA suture.
[0089] Example 2
[0090] This embodiment provides a method for preparing a suture thread based on controllable magnetic voltage and electricity, comprising the following steps:
[0091] 3 g of cobalt ferrite nanoparticles were added to 40 mL of sodium oleate, 1 mol / L hydrochloric acid was added to adjust the pH to 3.5, and the mixture was slowly precipitated and dried at 60°C to obtain oleic acid-coated cobalt ferrite nanoparticles; 234.6 g of oleic acid-coated cobalt ferrite nanoparticles were dispersed in 20 mL of ethanol, and then mixed with 20 mL of ethanol solution containing tetrabutyl titanate (the concentration of tetrabutyl titanate was 0.02 mol / L) by ultrasonic stirring, and 10 mL of an aqueous solution containing sodium chloride and potassium acetate (the concentration of potassium chloride was 0 .01mol / L, the concentration of potassium acetate is 0.01mol / L), stirring until uniform to obtain a mixed solution; placing the mixed solution in a 60°C water bath, adding acetic acid solution to adjust the pH to 3-4 and then standing for 2 hours, then maintaining the temperature at 90°C for 6 hours, and then maintaining it at 120°C for 12 hours, and then sintering the obtained product at 600°C for 6 hours, and finally preparing a magnetostrictive filler with a core-shell structure, i.e., potassium sodium titanate-cobalt ferrite core-shell particles (the core material is cobalt ferrite, and the shell material is potassium sodium titanate);
[0092] 10 g of L-polylactic acid and 1 g of potassium sodium titanate-cobalt ferrite core-shell particles were added to 100 mL of dichloromethane, and the mixture was stirred at a speed of 180 rpm for 120 min to obtain a mixed solution, and the mixed solution was vacuumed to remove bubbles;
[0093] The vacuum-treated mixed solution was extruded into a coagulation bath solution (specifically, a mixed solution of isopropanol and deionized water, with a volume ratio of isopropanol to deionized water of 2:8) and allowed to stand for 12 hours, while the dichloromethane was exchanged and the mixture was shaped to obtain a linear composite material;
[0094] The linear composite material was dried at 60°C for 36 hours to completely remove the residual dichloromethane and the residual coagulation bath solution, and then annealed and crystallized at 120°C for 6 hours, and then corona polarized at 30°C for 30 minutes with a voltage intensity of 8 kV to excite the piezoelectric properties of potassium sodium titanate in the linear composite material to obtain the suture core material;
[0095] The surface of the suture core material is plasma treated for 15 minutes, and then 10 g of the plasma-treated suture core material is immersed in 200 mL of benzophenone ethanol solution (wherein the mass content of benzophenone is 20 wt%) for 25 minutes, and then immersed in 100 mL of hydrogel precursor solution (specifically an aqueous solution containing 50 wt% [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide and 1 wt% α-ketoglutaric acid) for 10 minutes. After taking out, it is irradiated with light of 320 nm wavelength for photocuring for 120 minutes, and then a layer of hydrogel skin is modified on the surface of the suture core material to reduce friction and protein adsorption to obtain the suture.
[0096] Determine the strength of the applied magnetic field, change the frequency of the magnetic field, and collect the response voltage of the suture line. Specifically, control the distance between the magnetic field and the suture line test module to adjust the magnetic field strength to 200mT, change the magnetic field strength in a cycle, and ensure that the magnetic field cuts the suture line regularly to achieve regular electrical release. A voltage of 200mV can be released at a frequency of 3Hz.
[0097] Example 3
[0098] This embodiment provides a method for preparing a suture thread based on controllable magnetic voltage and electricity, comprising the following steps:
[0099] 234.8 g of oleic acid-coated nickel ferrite nanoparticles (the preparation method thereof is referred to in Example 2) were dispersed in 20 mL of ethanol, and then mixed with 20 mL of an ethanol solution containing tetrabutyl titanate (the concentration of tetrabutyl titanate was 0.02 mol / L) by ultrasonic stirring, and 10 mL of an aqueous solution containing sodium chloride and potassium acetate (the concentration of sodium chloride was 0.01 mol / L, and the concentration of potassium acetate was 0.01 mol / L) was slowly added dropwise until the mixture was stirred evenly to obtain a mixed solution; the mixed solution was placed in a 60° C. water bath, acetic acid solution was added to adjust the pH to 3-4, and then allowed to stand for 2 h, and then the temperature was maintained at 90° C. for 6 h, and then maintained at 120° C. for 12 h, and the obtained product was placed at 600° C. for sintering for 6 h, and the final product was a magnetostrictive filler with a core-shell structure, i.e., potassium sodium titanate-nickel ferrite core-shell particles (the core material was nickel ferrite, and the shell material was potassium sodium titanate);
[0100] 10 g of cellulose and 1 g of potassium sodium titanate-nickel ferrite core-shell particles were added to 100 mL of dichloromethane, and the mixture was stirred at a speed of 180 rpm for 120 min to obtain a mixed solution, and the mixed solution was vacuumed to remove bubbles;
[0101] The mixed solution after vacuum treatment is extruded into a coagulation bath solution (specifically a mixed solution of isopropanol and deionized water, the volume ratio of isopropanol to deionized water is 3:7) and stays for 12 hours, while exchanging the dichloromethane and achieving shaping, to obtain a linear composite material;
[0102] The linear composite material was dried at 60°C for 6 h to completely remove the residual dichloromethane and residual coagulation bath solution, and then annealed and crystallized at 120°C for 6 h, and then corona polarized at 30°C for 30 min with a voltage intensity of 8 kV to stimulate the piezoelectric properties of cellulose in the composite material.
[0103] The surface of the suture core material is plasma treated for 15 minutes, and then 1 g of the plasma-treated suture core material is immersed in 20 mL of benzophenone ethanol solution (wherein the mass content of benzophenone is 10 wt%) for 25 minutes, and then immersed in 20 mL of hydrogel precursor solution (specifically an aqueous solution containing 35 wt% [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide and 5 wt% α-ketoglutaric acid) for 20 minutes. After being taken out and irradiated with light at a wavelength of 350 nm for photocuring for 45 minutes, a layer of hydrogel skin is modified on the surface of the suture core material to reduce friction and protein adsorption, thereby obtaining the suture.
[0104] Determine the strength of the applied magnetic field, change the frequency of the magnetic field, and collect the response voltage of the suture line. Specifically, control the distance between the magnetic field and the suture line test module to adjust the magnetic field strength to 100mT, and change the magnetic field strength in a cycle to ensure that the magnetic field cuts the suture line regularly and achieves regular electrical release. A voltage of 150mV can be released at a frequency of 3Hz.
[0105] Example 4
[0106] This embodiment provides a method for preparing a suture thread based on controllable magnetic voltage and electricity, comprising the following steps:
[0107] 1482.4 mg of polydopamine-wrapped gallium-antimony alloy nanoparticles (the preparation method of which is described in Example 1) were dispersed in 40 mL of ethanol, and then evenly mixed with 20 mL of an ethanol solution containing boron nitride nanotubes (the concentration of the boron nitride nanotubes was 0.01 mol / L) by ultrasonic stirring, and slowly stirred for 144 h in a light-proof environment to obtain a magnetostrictive filler with a core-shell structure, i.e., boron nitride nanotube-gallium-antimony alloy core-shell particles (the core material is gallium-antimony alloy, and the shell material is boron nitride nanotubes).
[0108] 10 g of collagen and 1 g of boron nitride nanotube-gallium antimony alloy core-shell particles were added to 100 mL of phosphate buffer, and the mixture was stirred at 240 rpm for 120 min to obtain a mixed solution, and the mixed solution was vacuumed to remove bubbles;
[0109] The mixed solution after vacuum treatment was extruded into a coagulation bath solution (specifically, a mixed solution of ethanol and deionized water, with a volume ratio of ethanol to deionized water of 1:19) and allowed to remain there for 12 hours, while the phosphate buffer was exchanged and the solidification was achieved, thereby obtaining a linear composite material;
[0110] The linear composite material was dried at 60°C for 36 hours to completely remove the residual phosphate buffer and the residual coagulation bath solution, then annealed and crystallized at 120°C for 6 hours, and corona polarized at 30°C for 30 minutes with a voltage intensity of 30 kV to excite the piezoelectric properties of collagen in the linear composite material to obtain a suture core material;
[0111] The surface of the suture core material was plasma treated for 15 minutes, and then 4 g of the plasma-treated suture core material was immersed in 250 mL of an ethanol solution of benzophenone (wherein the mass content of benzophenone was 15 wt%) for 25 minutes, and then immersed in 300 mL of a hydrogel precursor solution (specifically an aqueous solution containing 25 wt% acrylamide and 1 wt% photoinitiator 2959) for 5 minutes. After being taken out and irradiated with light at a wavelength of 325 nm for photocuring for 180 minutes, a layer of hydrogel skin was modified on the surface of the suture core material to reduce friction and protein adsorption, thereby obtaining the suture.
[0112] Determine the strength of the applied magnetic field, change the frequency of the magnetic field, and collect the response voltage of the suture line. Specifically, control the distance between the magnetic field and the suture line test module to adjust the magnetic field strength to 100mT, change the magnetic field strength cyclically, and ensure that the magnetic field cuts the suture line regularly to achieve regular electrical release. A voltage of 20mV can be released at a frequency of 3Hz.
[0113] Example 5
[0114] This embodiment provides a method for preparing a suture thread based on controllable magnetic voltage and electricity, comprising the following steps:
[0115] 234.6 mg of nickel ferrite nanoparticles wrapped with polydopamine (the preparation method thereof is referred to Example 1) were dispersed in 20 mL of ethanol, and then uniformly mixed with 20 mL of an ethanol solution containing lead zirconate titanate (wherein the concentration of lead zirconate titanate was 0.02 mol / L) by ultrasonic stirring, and slowly stirred for 72 h in a light-proof environment, and the final product prepared was a magnetostrictive filler having a core-shell structure, namely, lead zirconate titanate-nickel ferrite core-shell particles (the core material was nickel ferrite, and the shell material was lead zirconate titanate);
[0116] 10 g of 3-hydroxybutyric acid-co-3-hydroxyvaleric acid and 1 g of lead zirconate titanate-nickel ferrite core-shell particles were added to 100 mL of dichloromethane, and the mixture was stirred at a speed of 300 rpm for 120 min to obtain a mixed solution, and the mixed solution was vacuumed to remove bubbles;
[0117] The mixed solution after vacuum treatment is extruded into a coagulation bath solution (specifically, a mixed solution of ethanol and deionized water, with a volume ratio of ethanol to deionized water of 2:8) and left for 12 hours to exchange the dichloromethane and achieve shaping, thereby obtaining a linear composite material;
[0118] The linear composite material was dried at 60°C for 36 hours to completely remove the residual dichloromethane and the residual coagulation bath solution, then annealed and crystallized at 120°C for 6 hours, and corona polarized at 30°C for 30 minutes with a voltage intensity of 10 kV to excite the piezoelectric properties of 3-hydroxybutyric acid-co-3-hydroxyvaleric acid in the linear composite material to obtain the suture core material;
[0119] The surface of the suture core material was plasma treated for 15 minutes, and then 3 g of the plasma-treated suture core material was immersed in 200 mL of an isopropanol solution of benzophenone (wherein the mass content of benzophenone was 10 wt%) for 25 minutes, and then immersed in 100 mL of a hydrogel precursor solution (specifically an aqueous solution containing 25 wt% acrylamide and 1 wt% photoinitiator 2959) for 10 minutes. After being taken out and photocured by irradiation with light of a wavelength of 375 nm for 90 minutes, a layer of hydrogel skin was modified on the surface of the suture core material to reduce friction and protein adsorption, thereby obtaining the suture.
[0120] Determine the strength of the applied magnetic field, change the frequency of the magnetic field, and collect the response voltage of the suture line. Specifically, control the distance between the magnetic field and the suture line test module to adjust the magnetic field strength to 100mT, change the magnetic field strength cyclically, and ensure that the magnetic field cuts the suture line regularly to achieve regular electrical release. A voltage of 20mV can be released at a frequency of 3Hz.
[0121] Example 6
[0122] This embodiment provides a method for preparing a suture thread based on controllable magnetic voltage and electricity, comprising the following steps:
[0123] 234.86 mg of cobalt ferrite nanoparticles wrapped with polydopamine (the preparation method thereof is referred to Example 1) are dispersed in 20 mL of ethanol, and then mixed with 20 mL of ethanol solution containing tetrabutyl titanate (wherein the concentration of tetrabutyl titanate is 0.03 mol / L) by ultrasonic stirring, and 10 mL of aqueous solution containing barium acetate (the concentration of barium acetate is 0.02 mol / L) is slowly added dropwise until the mixture is stirred evenly to obtain a mixed solution; the mixed solution is placed in a 60° C. water bath, acetic acid solution is added to adjust the pH to 3-4, and then allowed to stand for 2 h, then the temperature is maintained at 90° C. for 6 h, and then maintained at 120° C. for 12 h, and the product is placed at 600° C. for sintering for 6 h, and the final product is a magnetostrictive filler with a core-shell structure, namely, barium titanate-cobalt ferrite core-shell particles (the core material is cobalt ferrite, and the shell material is barium titanate) ;
[0124] 10 g of N-vinylglycine and 1 g of barium titanate-cobalt ferrite core-shell particles were added to 100 mL of ethyl acetate, and the mixture was stirred at 120 rpm for 120 min to obtain a mixed solution, and the mixed solution was evacuated to remove bubbles;
[0125] The mixed solution after vacuum treatment is extruded into a coagulation bath solution (specifically a mixed solution of isopropanol and deionized water, the volume ratio of isopropanol to deionized water is 3:7) and stays for 12 hours, while exchanging ethyl acetate to achieve shaping, to obtain a linear composite material;
[0126] The linear composite material was dried at 60°C for 36 hours to completely remove the residual ethyl acetate and the residual coagulation bath solution for 36 hours, then annealed and crystallized at 180°C for 6 hours, and corona polarized at 30°C for 30 minutes with a voltage intensity of 20 kV to excite the piezoelectric properties of N-vinylglycine in the linear composite material to obtain the suture core material;
[0127] The surface of the suture core material is plasma treated for 15 minutes, and then 0.5 g of the plasma-treated suture core material is immersed in 10 mL of ethanol solution of benzophenone (wherein the mass content of benzophenone is 10 wt%) for 25 minutes, and then immersed in 10 mL of hydrogel precursor solution (specifically an aqueous solution containing 35 wt% [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide and 3 wt% α-ketoglutaric acid) for 30 minutes. After being taken out and irradiated with light of 400 nm wavelength for photocuring for 180 minutes, a layer of hydrogel skin is modified on the surface of the suture core material to reduce friction and protein adsorption, thereby obtaining the suture.
[0128] Determine the strength of the applied magnetic field, change the frequency of the magnetic field, and collect the response voltage of the suture line. Specifically, control the distance between the magnetic field and the suture line test module to adjust the magnetic field strength to 100mT, change the magnetic field strength in a cycle, and ensure that the magnetic field cuts the suture line regularly to achieve regular electrical release. A voltage of 50mV can be released at a frequency of 3Hz.
[0129] In summary, the present invention provides a suture and a preparation method thereof. The suture provided by the present invention is adapted to the tissue modulus, has low friction, and maintains the basic characteristics of piezoelectric materials while also having good magnetic field response electrical stimulation capabilities, and has non-invasive electrical stimulation characteristics with controllable response intensity, and can generate electrical stimulation under the induction of a wireless magnetic field, thereby promoting cell migration and proliferation, and promoting wound healing. And because the suture has low friction, it will basically not cause further friction damage to the wound when the suture is removed, and has broad application prospects. In addition, piezoelectric materials and magnetostrictive fillers are added to a solvent, stirred and mixed to obtain a mixed solution, and bubbles are removed by vacuuming, and a suture with wireless magnetic field stimulation electrical release is prepared by extrusion, coagulation bath solution exchange, drying (the purpose is to remove residual solvent and coagulation bath solution), annealing, corona polarization, and growth of a hydrogel layer. The preparation method provided by the present invention is simple and fast, the raw materials are easily available, the process flow is short, and it is easy to operate.
[0130] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A suture, characterized in that: The suture comprises a suture core material and a hydrogel modified on the surface of the suture core material; The suture core material comprises the following components by mass: 1 to 1000 parts of piezoelectric material and 1 to 1000 parts of magnetostrictive filler.
2. The suture according to claim 1, characterized in that: The hydrogel is coated on the surface of the suture core material.
3. The suture according to claim 1, characterized in that: The piezoelectric material includes at least one of boron nitride nanotubes, 3-hydroxybutyric acid-co-3-hydroxyvaleric acid, collagen, diphenylalanine, N-vinylglycine, poly(L-lactic acid), cellulose, polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene, lead zirconate titanate, barium titanate and potassium sodium titanate.
4. The suture according to claim 1, characterized in that: The magnetostrictive filler has a core-shell structure, wherein the core material includes at least one of iron-nickel alloy, cobalt-iron alloy, ferrite, rare earth alloy and gallium-antimony alloy, and the shell material includes at least one of boron nitride nanotubes, 3-hydroxybutyric acid-co-3-hydroxyvaleric acid, collagen, diphenylalanine, N-vinylglycine, L-polylactic acid, cellulose, polyvinylidene fluoride, polyvinylidene fluoride-trifluoroethylene, lead zirconate titanate, barium titanate and potassium sodium titanate.
5. A method for preparing the suture thread according to claim 1, characterized in that: The steps include: Adding 1 to 1000 parts by mass of piezoelectric material and 1 to 1000 parts by mass of magnetostrictive filler into a solvent to obtain a mixed solution; The mixed solution is extruded into a coagulation bath solution and allowed to remain there for a preset time, and the solvent is exchanged while being shaped to obtain a linear composite material; The linear composite material is dried and annealed, and then corona polarized to obtain a suture core material; The suture is obtained by modifying the surface of the suture core material with hydrogel.
6. The preparation method according to claim 5, characterized in that: The ratio of the volume of the solvent to the total mass of the piezoelectric material and the magnetostrictive filler is (50-150) mL: (10-50) g; The solvent includes at least one of dimethyl sulfoxide, N-methylpyrrolidone, dimethylformamide, isopropanol, phosphate buffer and ethanol.
7. The preparation method according to claim 5, characterized in that: The coagulation bath solution includes at least one of deionized water, phosphate buffer, methanol, ethanol and isopropanol; and the preset time is 1 to 12 hours.
8. The preparation method according to claim 5, characterized in that: The drying temperature is 60-120° C., and the drying time is 6-36 hours; the annealing temperature is 90-180° C., and the annealing time is 1-12 hours.
9. The preparation method according to claim 5, characterized in that: The conditions of the corona poling are: temperature of 25-50° C., time of 10-60 min, and voltage of 5-30 kV.
10. The preparation method according to claim 5, characterized in that: The method further includes a step of vacuuming the mixed liquid before the mixed liquid is extruded into the coagulation bath solution and allowed to remain there for a preset time.
Citation Information
Cited By
Anti-infection and healing-promoting difunctional electroactive suture line as well as preparation method and application thereof
CN122163866A